ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN DISIPLIN KERJA KARYAWAN NON PNS PADA RSUD dr. FAUZIAH BIREUEN TAHUN 2021 - Safrizal Safrizal; Bungamari Sembiring; Fithri Handayani Lubis (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Work discipline is defined as an attitude or behavior of an employee in an organization to always obey, respect, and respect various rules and norms that have been set by the organization in order to achieve organizational goals. The type of research used is quantitative research with a survey method that aims to analyze the factors related to the work discipline of non-civil servants at RSUD dr. Fauziah Bireuen in 2021. This research will be carried out at RSUD dr. Fauziah Bireuen from November 2021 to March 2022. The sample selection in this study was carried out using the Slovin formula, based on this formula the number of samples was 90 non-civil servants. The sampling method used is consecutive sampling. Variables of Supervision System, Provision of Sanctions, Rewards/Reward Services and Leadership Exemplary related to Work Discipline of Non-PNS Employees At RSUD dr. Fauziah Bireuen 2021. The most dominant variable with non-civil servant employee work discipline is the supervisory system and has 5,859 times the opportunity to improve work discipline for non-civil servant employees at RSUD dr. Fauziah Bireuen. It is necessary to establish a supervisory system to monitor and evaluate the work discipline of Non-PNS employees, Imposing sanctions on employees who violate the rules, especially those related to work discipline and Adjusting the provision of rewards/services to the workload conditions and work discipline of non-PNS employees at RSUD dr. Fauziah Bireuen.